Level up : live performance and creative process in grime music - De Lacey, Alex (Abingdon, Oxon ; New York : Routledge, 2023)
"Grime music has been central to British youth culture since the beginning of the 21st century. Performed by MCs and DJs, it is an Afrodiasporic form that developed on street corners, on pirate radio and at raves. Level Up: Live Performance and Creative Process in Grime Music offers the first long-form ethnographic study of grime practice; it questions how and why artists do what they do; and it asks what this can tell us about creative process and improvisation more widely. Based on research conducted from 2015 to 2020 in London's grime scene-facilitated by the author's long-standing role as a DJ and broadcaster-this book explores the form's emergence before taking a magnifying glass to the contemporary scene and its performance protocol, exploring the practice of key artists and their crews living and working in the city. The resultant model of creative interaction provides a comprehensive mapping of collective social learning in London's informal cityscape, offering new ways to conceptualise improvisatory practice within ensembles"--
140 BPM Way of Life -- Foundations -- Improvisation and Group Process -- The Through Ball -- Pirate Mentality -- Levelling Up.
Keywords: Grime (Music) -- England -- London -- History and criticism; Black people -- England -- London -- Music -- History and criticism; MUSIC / Genres & Styles / Rap & Hip Hop; MUSIC / History & Criticism